Hubungan Teknik Menyusui dengan Kejadian Mastitis Pada Ibu Nifas di Klinik Abi Ummi DW Sarmadi Palembang - Sunirah, Sunirah; Solekah, Umi; Herdiani, Rini (JURNAL KESEHATAN TERAPAN, 2024)
he technique of breastfeeding is a way that comply with health standards do not cause any side effects and are also useful. This research aims to know The Relationship of Nursing Techniques With Mastitis On The Post Partum Mother At Clinic Abi Ummi DW Sarmadi Palembang. The sample in this research totalled 20 respondent. Typeof this research is a survey of analytical methdods approach of cross sectional. The research been funded on 01-31 August 2022. Sampling techniques in the study using the technique of Accidental Sampling. The result of the analysis of post partum mother bivariat who perform nursing technique right with Genesis mastitis 1 person (8.3%), the correct breastfeeding technique with mastitis does not occur 11 people (91.7%). While the mother is breastfeeding technique that do partururition is wrong with the incidence of mastitis 2 people (25%), breastfeeding technique is wrong with events not happening mastitis 6 people (75%). The result of the rest statistic chi-square obtain p_value 0.701 > 0.05 means that statistically there is no meaningful relationship between feeding technique with mastitis in Clinics Abi Ummi DW Sarmadi Palembang to other researchers who subsequently could use different methods and test reproduce samples research.